Applying classification methodology to high-consequence firesetting - Nanayakkara, Vindya (Psychology, crime & law, 2020)
Although classification research has improved our understanding about different types of firesetters, very little is known about those responsible for the most injurious or destructive fires. This study explored variables associated with high-consequence firesetting in an Australian sample (n = 114). Data across 41 variables were subject to multidimensional scaling (MDS) and principle component analysis. Five types of high-consequence firesetting were identified: (1) Intimate Partner Violence, (2) Hopeless Endangerment, (3) Instrumental Gain, (4) Vandalism, and (5) Fire Interest. Firesetting in the first two types involved individuals with increased rates of past violence, fewer instances of previous firesetting, increased psychiatric morbidity and fires directed at people (person-centred targets). In comparison, individuals represented in the latter two types were younger, focused on object-related targets and had engaged in repeated firesetting. Implications for investigating deliberate firesetting and assessing and managing the risk of deliberate firesetting were discussed.